Emotional freedom techniques in mental health care: evidence review, gaps, and future directions - Sebastian Salicru (Academia Mental Health & Well-Being)
Clinical Emotional Freedom Techniques (EFT) is an evidence-based, self-help, and cost-effective therapy used by millions worldwide since its development in the 1980s. It integrates energy psychology, acupressure, exposure therapy, and cognitive-behavioral elements to treat various psychological and medical conditions. Like other fourth-wave or mind–body therapies incorporating somatic components, such as eye movement desensitization and reprocessing (EMRD), EFT has gained popularity among practitioners in the last two decades for the treatment of somatic symptoms of stress, anxiety, depression, childhood trauma, and adult survivors and caregivers during natural and human-made disasters, including post-traumatic stress disorder (PTSD). Despite over 100 published studies reporting its efficacy, EFT has historically been controversial and, to date, has faced opposition to its adoption by the scientific community in clinical settings for various reasons, including concerns about its efficacy, alleged rapidity, and questioned mechanisms. This inconsistency in the literature creates gaps in conceptual, theoretical, empirical, methodological, and practical bases. This review addresses these gaps by providing a critical and balanced overview of current EFT research from a scientist–practitioner perspective. PubMed, PsycINFO, and Google Scholar databases were used to search the literature. Findings outline EFT’s emerging concepts, recent developments, and latest criticisms. Conclusions propose a potential research agenda and future practical applications of EFT within the current global mental health crisis (GMHC) context.